REVALORIFICAREA DISCURSULUI TEOLOGIC DESPRE CORP ÎN DIALOGUL DINTRE RELIGIE ȘI ȘTIINȚĂ - CHIRILOAEI, Sergiu - Bogdan (Studia Universitatis Babeș-Bolyai Theologia Graeco-Catholica Varadiensis, 2024)
Re-evaluating the Theological Discourse about Body and Soul in the Dialogue between Religion and Science. Originally, Greek culture and Jewish tradition, the two sources of Western culture, perceived human being in a unitary way, the ontological dualism of body and soul being generally absent. The individual was harmoniously identified with his own body, in a close relationship with the world and other individuals. The difference between classical Greek thought and biblical thought is subtle. In the case of the Jewish tradition we cannot speak of a human being who unites two worlds within himself, that of spirit and that of flesh, but of a being who can choose between the alliance with God and life, or the rupture of communion and death. The proof we have is the penetration of soul`s immortality into the Christian doctrine.